EXPERIMENTAL FRAGMENTATION OF CRYSTAL- AND VESICLE-BEARING SILICIC MELTS - Martel C.; Dingwell D.B.; Spieler O.; Pichavant M.; Wilke M. (My University, 2001)
We experimentally investigate the effect of crystals on the fragmentation behavior of a three-phase (melt+gas+crystals) system under rapid decompression. Starting materials are cylinders of hydrated haplogranite melts containing alumina crystals that are placed at 6-30 MPa and 600-800C in a fragmentation bomb for foaming. Subsequently, these bubble- and crystal-bearing melts are rapidly decompressed (within <1 s) to room pressure and temperature and the fragmented particles are recovered for analysis. We investigated the influence of the crystal size (~70-350 m in diameter), the crystal content (20-95 vol.%), and the magnitude of the decompression (6-30 MPa) on the fragment sizes. Crystals down to 70 m in diameter have a strong influence on the fragment size distribution by defining fragments made of single crystals. Increasing the crystal content in the starting material leads to an increase of the average size of the fragments. Increasing the magnitude of the decompression generates finer fragments. Fragmentation threshold or dynamic tensile strength ranges from ~10 MPa for crystal-poor samples up to >30 MPa for phenocryst- and microlite-bearing samples.